Revisiting step instabilities on crystal surfaces. Part I: The quasistatic approximation. (November 2021) - Guin, L.; Jabbour, M.E.; Triantafyllidis, N.
Abstract: Epitaxial growth on a surface vicinal to a high-symmetry crystallographic plane occurs through the propagation of atomic steps, a process called step-flow growth. In some instances, the steps tend to form close groups (or bunches), a phenomenon termed step bunching, which corresponds to an instability of the equal-spacing step propagation. Over the last fifty years, various mechanisms have been proposed to explain step bunching, the most prominent of which are the inverse Ehrlich–Schwoebel effect (i.e., the asymmetry which favors the attachment of adatoms from the upper terrace), elastically mediated interactions between steps (in heteroepitaxy), step permeability (in electromigration-controlled growth), and the chemical effect (which couples the diffusion fields on all terraces). Beyond the discussion of the influence of each of these mechanisms taken independently on the propensity to bunching, we propose a unified treatment of the effect of these mechanisms on the onset of the bunching instability, which also accounts for their interplay. This is done in the setting of the so-called quasistatic approximation, which by permitting mostly analytical treatment, offers a clear view of the influence on stability of the combined mechanisms. In particular, we find that the Ehrlich–Schwoebel effect, elastic step-interactions and the chemical effect combine in a quasi-additive fashion, whereas step permeability is neither stabilizing nor destabilizing per se but changes the relative influence of the three aforementioned mechanisms. In a companion paper, we demonstrate and discuss the importance of another mechanism, which we call the dynamics effect, that emerges when relaxing the simplifying but questionable quasistatic approximation.